Mitigating the risks of indirect land use change (ILUC) related deforestation from industrial palm oil expansion by sharing land access with displaced crop and cattle farmers - Badrul Azhar; Nobilly, Frisco; Lechner, Alex M.; Tohiran, Kamil Azmi; Maxwell, Thomas M. R.; Raja Zulkifli; Kamel, Mohd Fathil; Oon, Aslinda (Elsevier, 2021)
The European Commission (EC) is critical of palm oil production as it has a high indirect land-use change (ILUC) risk from industrial palm oil expansion pressuring landless/displaced farmers to clear tropical forests. Major palm oil-producing countries such as Indonesia and Malaysia are claiming that the EC’s decision will cause unwarranted obstacles to the adoption of sustainable practices in the palm oil industry and obstruct free trade. To date, in responding to the EC, both Indonesia and Malaysia have yet to develop a national strategy that mitigates the risks of ILUC caused by industrial palm oil expansion. Hence, we propose these major palm oil-producing countries reform their land policy by making it compulsory for plantation companies to share production land with landless/displaced farmers. This strategy could prevent farmers from clearing more tracts of tropical forest and encourage them to use immature and mature areas of palm oil stands for crop and cattle farming, respectively. To guide this strategy, we performed Monte Carlo simulations to predict palm oil production land area and then estimate the land which could be allocated for crop and cattle farming at global-, country-, and plantation-scales. Besides mitigating further deforestation in the tropics, the crop and livestock integration strategy can boost food security and reduce the use of chemical herbicides in palm oil-producing countries. The strategy is consistent with palm oil certification schemes in terms of ensuring social and environmental sustainability. Palm oil-producing countries should implement the strategy to address ILUC risk while consumer countries should demand producers use such strategy.